If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4n + 2) = 9 Reorder the terms: -3(2 + 4n) = 9 (2 * -3 + 4n * -3) = 9 (-6 + -12n) = 9 Solving -6 + -12n = 9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -12n = 9 + 6 Combine like terms: -6 + 6 = 0 0 + -12n = 9 + 6 -12n = 9 + 6 Combine like terms: 9 + 6 = 15 -12n = 15 Divide each side by '-12'. n = -1.25 Simplifying n = -1.25
| 4x^2-x+13=7x+10 | | 2x^2+13x=6x+30 | | -(5y+3)-(-4-4)=-2 | | 3x^2-6+11=0 | | 10x^3+12x^2-14x=0 | | 2.1x=18.9 | | 16x^2-46x+28=0 | | 4x^2-13x-35=0 | | 7x^2+175=0 | | 4w-6=6w-20 | | 13+b=24 | | 5.64+34.6+.058+4= | | n-41=60 | | -15+x=8(x-6)-2 | | 118-7x=20x+22 | | 61-s=30 | | -56=-21t | | .75x-2=16 | | q+7=15 | | 22=10+b | | 14-9x=41-30x | | 6y+32=32y-20 | | 42-7x=2x+22 | | .12x+.1(15000-x)=500 | | .6x+5=17 | | 2c-7=c/2+5 | | x+2y=37 | | -14a-28=0 | | 172-5x=22x+16 | | x/4+5=x/2+1 | | 4/5+3=18 | | x+x+1.5+x+x+1.5=17 |